(untitled) (Research, Society and Development, 2022)
This article presents an integrative literature review aimed at reviewing the relationship between endometriosis and female infertility between the years 2016-2022. In this type of study, the integrative review helps to obtain, identify and analyze a specific topic in the literature. Thus, the objective of this work is to extract information from the updated literature through articles selected between the years 2016-2022 in empirical categories called: “Relationship of endometriosis with female infertility”; “Early diagnosis of endometriosis and the influence on female infertility”; "Treatment of endometriosis and the impact on women’s health", in order to relate endometriosis to female infertility in an integrative review. The conclusion is, therefore, that health professionals, who manage the treatment of endometriosis, should be attentive to early diagnosis, whether in the form of a questionnaire or laboratory tests, treatment and, consequently, the quality of women’s life.